INFLUENCE OF MANURE AND FERTILIZERS ON SOME CHEMICAL AND BIOLOGICAL PROPERTIES OF SOIL Am> WATER OF A BRACKISHWATER FISH POND - Chattopadhyay, G N; Mandal, L N (Indian Journal of Fisheries, 2011)
The change* in chemical and biological properties of soil and water of abrackishwater flish pond for one year, effected by a combined application of cowdung,urea and single super phosphate, showed that the behaviour of differentnutrient elements in water and soil phase of the pond is largely influenced by prevailingwater salinity levels. Rapid disappearance of the added nutrients fromavailable forms suggested that the fertilization period in such ponds should bemade short. Application of manure and fertilizers was found to be effective inincreasing the production of plankton and especially soil flora. Adverse effects ofmanuring with raw cowdung on the growth of bottom fauna indicated that use ofcomposted manures might be more beneficial for such ponds.